School counselors' assessment of the psychological counseling and guidance services they offer at their schools - Yuksel-Sahin, Fulya (ELSEVIER SCIENCE BV, 2012)
The study aims to obtain an academic, vocational, personal, and social assessment of school counselors of the psychological counseling and guidance (PCG) services they offer at their schools. It also evaluates the suggestions of the school counselors as to the conditions required to make the PUG practices M their schools inure adequate. The research involves dominant status concurrent design within in-phase mixed design as a mixed research design category. The sample group consists of 49 school counselors serving at elementary and secondary levels in Istanbul. School Psychological Counseling and Guidance Services Assessment Form and Personal Information Form were used to collect data. The collected data were subjected to quantitative and qualitative analyses. Frequency (f) and percentage (%) calculations were performed for quantitative analysis. Furthermore, bivariate chi-square (X-2) test was performed using the crosstabs technique. Descriptive analysis was made for qualitative analysis. The research results showed that the school counselors offer personal PCG services at a greater level and academic and vocational PCG services at similar levels. Of the school counselors stating that they offer an adequate level of PCG services, 75% are employed at secondary level while 44% work at elementary level. Of the school counselors stating that they offer an adequate level of PCG services, 69.7% are female and 37.5% are male.
Keywords: Psychological Counseling and Guidance; School Counselor; Education & Educational Research